Expression of the cAMP Binding Protein EPAC1 in Thyroid Tumors and Growth Regulation of Thyroid Cells and Thyroid Carcinoma Cells by EPAC Proteins - Broecker-Preuss, M.; Baten, J.; Sheu-Grabellus, S.-Y.; Görges, R.; Bockisch, A.; Schmid, K. W.; Führer, D.; Mann, K. (Hormone and Metabolic Research, 2015)
The thyrotropin receptor-cAMP pathway is central in growth regulation of thyroid cells and thyroid tumorigenesis, and it regulates expression of thyroid specific genes. Recently, 2 new protein kinase A-independent cAMP effectors named EPAC1 and 2 were described that activate additional intracellular pathways. The aim of our study was to investigate the role of EPAC proteins in growth regulation of thyroid cells and thyroid carcinomas. EPAC1 expression was investigated immunohistochemically in tissues of various thyroid tumors. Utilizing MTT assay, the effect of EPAC stimulation on proliferation in thyroid carcinoma cells and in non-transformed rat FRTL5 cells was investigated. The activation of intracellular signaling pathways was examined by RAP pull-down assay and Western blots. EPAC1 expression was strong in non-oxyphilic follicular thyroid adenomas and carcinomas and in follicular papillary thyroid carcinomas. It was moderate in oxyphilic follicular tumors and classical and tall cell papillary carcinomas. In contrast, EPAC1 expression was low in poorly differentiated carcinomas and very low in anaplastic carcinomas. Thyroid carcinoma cell lines showed no or very weak EPAC1 expression and exhibited no growth-promoting effect after EPAC stimulation. Non-transformed rat FRTL5 cells were growth-stimulated by an EPAC-specific cAMP-analogue and showed EPAC-dependent activation of RAP, ERK, and p70S6 kinase. EPAC1 expression and cellular response to EPAC activation in rat FRTL5 cells reflect cellular responses to cAMP and TSH stimulation in non-transformed thyroid cells. In undifferentiated thyroid carcinomas, loss of EPAC1 expression may be in accordance with the loss of thyroid-specific functions and the loss of responsiveness of the TSHR-cAMP pathway.
Keywords: cAMP signaling; TSH receptor; thyroid carcinoma; exchange protein activated by cAMP